Development of ELISAs for diagnosis of acute typhoid fever in Nigerian children. - Jiin Felgner; Aarti Jain; Rie Nakajima; Li Liang; Algis Jasinskas; Eduardo Gotuzzo; Joseph M Vinetz; Fabio Miyajima; Munir Pirmohamed; Fatimah Hassan-Hanga; Dominic Umoru; Binta Wudil Jibir; et al. (Public Library of Science (PLoS), 2017)
Improved serodiagnostic tests for typhoid fever (TF) are needed for surveillance, to facilitate patient management, curb antibiotic resistance, and inform public health programs. To address this need, IgA, IgM and IgG ELISAs using Salmonella enterica serovar Typhi (S. Typhi) lipopolysaccharide (LPS) and hemolysin E (t1477) protein were conducted on 86 Nigerian pediatric TF and 29 non-typhoidal Salmonella (NTS) cases, 178 culture-negative febrile cases, 28 "other" (i.e., non-Salmonella) pediatric infections, and 48 healthy Nigerian children. The best discrimination was achieved between TF and healthy children. LPS-specific IgA and IgM provided receiver operator characteristic areas under the curve (ROC AUC) values of 0.963 and 0.968, respectively, and 0.978 for IgA+M combined. Similar performance was achieved with t1477-specific IgA and IgM (0.968 and 0.968, respectively; 0.976 combined). IgG against LPS and t1477 was less accurate for discriminating these groups, possibly as a consequence of previous exposure, although ROC AUC values were still high (0.928 and 0.932, respectively). Importantly, discrimination between TF and children with other infections was maintained by LPS-specific IgA and IgM (AUC = 0.903 and 0.934, respectively; 0.938 combined), and slightly reduced for IgG (0.909), while t1477-specific IgG performed best (0.914). A similar pattern was seen when comparing TF with other infections from outside Nigeria. The t1477 may be recognized by cross-reactive antibodies from other acute infections, although a robust IgG response may provide some diagnostic utility in populations where incidence of other infections is low, such as in children. The data are consistent with IgA and IgM against S. Typhi LPS being specific markers of acute TF.